Efectividad de la terapia cognitivo conductual focalizada en el trauma para el trastorno de estrés postraumático en niños y adolescentes - Orezzoli Mongrut, Franco Alberto (2024)
Post-traumatic stress disorder (PTSD) in children and adolescents is a global public health problem. The aim of this review was to evaluate the evidence on the effectiveness of Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) for PTSD in children and adolescents. A systematic search was conducted in databases such as Scopus and Web of Science from which 7 randomized controlled trials and 3 quasi-experimental trials published between 2010 and 2024 were extracted as a sample. These investigations examined TF-CBT in children between the ages of 3 and 17 years with a diagnosis or symptoms of PTSD. The total number of participants was n=1011 participants. Results indicate that TF-CBT achieves significant reductions in reexperiencing, avoidance, and arousal symptoms with medium to large effect sizes (d=0.51-2.64). Improvements were also found in comorbidities such as depression, anxiety, behavior, and parental impact. Therapeutic benefits were maintained at medium-term follow-up. TF-CBT appears as an effective and recommendable first-line treatment for children and adolescents with PTSD in various contexts. More studies are needed on its relative effectiveness versus other interventions.